Redesigning Cireng Chips Product Packaging in an Effort to Increase Brand Awareness - Syafikarani, Aisyi; Muthmainnah, Ligar; Nastiti, Nisa Eka; Purwaningtyas, Abigail Nike (Universitas Negeri Semarang, 2025)
Gorciuk is an MSME that produces Cireng Chips with tapioca as the raw material. One of the local ingredients that is gluten-free and the seasoning is without MSG. This product was initially only intended and served for children with disabilities who had to reduce Gluten and without MSG which is one of the addictive ingredients and is not recommended for excessive consumption. Now foods with low Gluten content and without MSG are also quite sought after because many consumers are starting to pay attention to healthy food. With the high interest of consumers in the market, Gorciuk has begun to expand the types of products produced. Currently, Gorciuk markets its products with 2 flavor choices, namely pecel seasoning and salted cheese. However, the high interest of consumers is still not balanced with a representative packaging design, therefore Gorciuk currently needs to redesign the Product Packaging that they sell in order to increase Brand Awareness. The current condition is that Gorciuk markets its products only with simple packaging in the form of ordinary plastic that is not attractive and does not characterize their own typical cireng chips. This obstacle is the reason for the PKM team in implementing the Packaging Design grant using the DKV principle at Gorciuk. The Community Service Team consisting of three lecturers and students will design and apply the principles of DKV to Gorciuk.